2014
DOI: 10.1128/iai.01255-13
|View full text |Cite
|
Sign up to set email alerts
|

Gut Adhesive Bacillus subtilis Spores as a Platform for Mucosal Delivery of Antigens

Abstract: Bacterial carriers for the mucosal delivery of antigens, particularly those capable of colonizing or invading through the mucosal epithelia, have been intensively investigated (1). Live bacterial vectors can be generated with attenuated pathogens, such as Salmonella and Listeria, or nonpathogenic commensal species, such as Lactococcus and Lactobacillus. Bacteria in the former group of are capable of inducing strong and long-lasting immune responses to passenger antigens but present serious safety concerns, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…The Bacillus counts in feces of the control rats as well as the rats fed only skim milk (T1) were found to be very low or sometimes non-detectable. The significant increment of the Bacillus counts after feeding of B. coagulans B37 and B. pumilus B9 in rats strongly supports the previous reports on use of gut-colonizing B. subtilis spores as a new platform for the mucosal delivery of vaccine antigens [ 32 ] as well as survivability of Bacillus clausii spores in the human gastrointestinal (GI) tract, and thereafter germination, outgrowth, and multiplication as vegetative forms following oral administration as spore-based probiotic formulation [ 33 ]. In the present study, the feeding of B. coagulans B37 revealed that the fecal Bacillus count remained stable for 10 days after withdrawal of feeding of B. coagulans B37.…”
Section: Resultssupporting
confidence: 86%
“…The Bacillus counts in feces of the control rats as well as the rats fed only skim milk (T1) were found to be very low or sometimes non-detectable. The significant increment of the Bacillus counts after feeding of B. coagulans B37 and B. pumilus B9 in rats strongly supports the previous reports on use of gut-colonizing B. subtilis spores as a new platform for the mucosal delivery of vaccine antigens [ 32 ] as well as survivability of Bacillus clausii spores in the human gastrointestinal (GI) tract, and thereafter germination, outgrowth, and multiplication as vegetative forms following oral administration as spore-based probiotic formulation [ 33 ]. In the present study, the feeding of B. coagulans B37 revealed that the fecal Bacillus count remained stable for 10 days after withdrawal of feeding of B. coagulans B37.…”
Section: Resultssupporting
confidence: 86%
“…They have previously served as effective adjuvants as well [15, 16, 34]. Bacillus subtilis spores (approximately 1.2 μm in length) are well uptaken by M cells, transported into Peyer’s patches, processed by antigen-presenting cells, presented to B cells or T cells, and are transported to other gut-associated lymphoid tissues (GALTs) and systemic lymphoid tissues [14, 35]. During this process, a series of antigen-specific immune responses are induced and abundant immune globulins are secreted by plasma cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that another P1-derived fragment generated in Bacillus subtilis, encompassing amino acids 39 to 512 and named P1 , is immunogenic in mice and induces antibodies that interfere with S. mutans adhesive properties in vitro (25). We furthermore demonstrated that a mucosal delivery system based on genetically modified B. subtilis spores that express P1 39 -512 in vivo induced specific antibodies in serum and saliva that interfered with S. mutans adhesion to abiotic surfaces without preventing bacterial aggregation (26). These findings highlight the need for an understanding of the immunological, structural, and functional characteristics of P1 39 -512 as an alternative to the full-length protein as a target antigen to generate protective immunity against dental caries.…”
mentioning
confidence: 91%